Protection of E-Money in Indonesia: A Viewpoint from Security Aspect - Mochtar, Dewi Astutty (International Journal of Psychosocial Rehabilitation, 2020)
This study was designed to provide the concept of legal protection for electronic money (e-money) holders from the misuse of e-money in the context of Indonesian constitutional reform. A normative research approach was employed in this study. The results of this study indicated a vacuum of legal protection for e-money holders in Indonesia. E-money abuse problems in Indonesia were regulated by Bank Indonesia (BI) under the regulation number 20/6/PBI/2018, in particular for e-money holders. This finding unveiled that legal protection controls against e-money holders were lacking in Indonesia. This was due to differences in e-money activities or processes from banking transactions. This study has served as a catalyst for legal protection of Indonesian e-money holders to avoid losses due to misuse of electronic money.